Relationship Between Neutrophil-to-Lymphocyte Ratio, D-Dimer and Troponin-I Values and Pulmonary Embolism Severity Index - Güzel, Murat; Özgen, Emre; Terzi, Özlem; Demir, Mehmet Tevfik; Yücel, Murat; Baydın, Ahmet (My University, 2019)
Aim: We aimed to determine whether Neutrophil-to-Lymphocyte Ratio (NLR), Monocyte-to-Lymphocyte Ratio (MLR), Platelet-to-Lymphocyte Ratio (PLR), D-dimer, and troponin values were correlated with the simplified Pulmonary Embolism Severity Index (sPESI) in patients diagnosed as having Pulmonary Embolism (PE) in the emergency room.Material and Methods: Forty-three patients diagnosed as having PE in the emergency department were divided into low and high-risk groups according to the sPESI. We investigated whether NLR, MLR, and PLR, d-dimer, troponin-I, and Pulmonary Artery Pressure (PAP) had any effect in determining the severity of PE. Also, patients were divided into groups as those with PAP 20 or 20 mm Hg, Systolic Blood Pressure (SBP) 100 or 100 mm Hg, and those receiving or not receiving thrombolytic treatment, and compared.Results: There was a statistically significant difference between patients with low sPESI (n10) and those with high sPESI (n33) in terms of age (p0.001), pulse (p0.016), oxygen saturation (p0.039), troponin-I (p0.029) and PAP (p0.032), but there was no difference between the groups in terms of NLR (p0.796), MLR (p0.656), PLR (p0.863), and d-dimer (p0.343). There was a statistically significant difference between patients who did (n6) and did not (n37) receive thrombolytic treatment in terms of troponin-I (p0.012), but there was no difference between the groups in terms of NLR (p0.861), MLR (p0.335), and PLR (p0.277).Conclusion: NLR, MLR, PLR and d-dimer levels were found not to be effective in determining the severity of PE. Troponin-I was associated with sPESI and was considered as an effective marker in determining the thrombolytic treatment.
Keywords: Biyoloji; Diş Hekimliği; Alerji; Anatomi ve Morfoloji; Androloji; Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Biyokimya ve Moleküler Biyoloji; Biyofizik; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Kalp ve Kalp Damar Sistemi; Hücre Biyolojisi; Klinik Nöroloji; Yoğun Bakım; Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tamamlayıcı ve Entegre Tıp; Tıbbi Etik; Tıbbi İnformatik; Tıbbi Laboratuvar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak; Burun; Boğaz; Patoloji; Pediatri; Periferik Damar Hastalıkları; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Tropik Tıp; Üroloji ve Nefroloji; Farmakoloji ve Eczacılık; Toksikoloji